PENGARUH SUBSTITUSI BONGGOL PISANG (MUSA PARADISIACA) DAN PERENDAMAN KITOSAN TERHADAP KANDUNGAN GIZI DAN MUTU TEMPE - Kusumaningsih, Purwaningtyas - (Jurnal Teknologi Pangan dan Gizi, 2021)
The present study was to evaluate nutrition of tempeh made from banana tuber as soybean substituted. The soy beans and banana tuber were soak in 2% of chitosan as preservative before being mixed. Three formulations of soybean and banana tuber mixture: 70%+30% (TB1); 60%+40% (TB2) and 50%+50% (TB3), were established. For each formulations the parameter were evaluated: water content, ash, protein, fat, carbohydrate, fiber and pH. The result of three formulas analysis will compare with the control (100% soybeans). The water content from three formulas were under Indonesia’s National Standard for tempeh (3144:2015), it was more than 65%. The substitution soybean with banana tuber was not influence of ash content compared with the control. Otherwise the protein were decrease in the three formulas. The lowest percentage of fat is showed in TB3. The best carbohydrate result was obtained in TB3. The highest percentage of fiber was obtained in TB3. The pH was decreased in three formulas. In the Least Significant Difference (LSD) analysis, substitute of soybeans with banana tuber and 2% chitosan treatment were influence the water content, protein, fat, fiber and pH.